Metformin: A promising option for the management of gestational diabetes mellitus – Exploring the benefits, challenges and clinical needs in the current management of gestational diabetes mellitus. (1st April 2022) - Bastian, Beenu; Smithers, Lisa Gaye; Davis, Warren; Pape, Alexia; Francois, Monique E.
Abstract : The incidence of gestational diabetes mellitus (GDM) is increasing. One in three women require insulin to achieve glycaemic targets in GDM. However, it is unclear whether insulin therapy alone is the most effective treatment for all women in achieving glycaemic control and preventing adverse pregnancy outcomes. Although no oral hypoglycaemic agents are approved for pregnancy in Australia, recent research indicates that metformin is effective in preventing adverse perinatal outcomes and may even have possible benefits in the long term. Furthermore, there appears to be a specific role for both metformin and insulin among the GDM population. Metformin provides an option to offer an individualised approach to treat GDM.